Trends in the Precipitation and Crystallization Behavior of Supersaturated Aqueous Solutions of Poorly Water‐Soluble Drugs Assessed Using Synchrotron Radiation. Issue 6 (21st March 2015) - Raina, Shweta A.; Eerdenbrugh, Bernard Van; Alonzo, David E.; Mo, Huaping; Zhang, Geoff G. Z.; Gao, Yi; Taylor, Lynne S.
<x xml:space="preserve">Abstract</x> Amorphous materials are high‐energy solids that can potentially enhance the bioavailability of poorly soluble compounds. A major impediment to their widespread use as a formulation platform is the tendency of amorphous materials to crystallize. The aim of this study was to evaluate the relative crystallization tendency of six structural analogues belonging to the dihydropyridine class, in an aqueous environment in the absence and presence of polymers, using wide‐angle X‐ray scattering synchrotron radiation and polarized light microscopy. The crystallization behavior of precipitates generated from supersaturated solutions of the active pharmaceutical ingredients was found to be highly variable ranging from immediate to several hours in the absence of polymers. Polymers with intermediate hydrophilicity/hydrophobicity were found to substantially delay crystallization, whereas strongly hydrophilic or hydrophobic polymers were largely ineffective. Nuclear magnetic resonance spectroscopy experiments supported the supposition that polymers need to have affinity for both the drug‐rich precipitate and the aqueous phase in order to be effective crystallization inhibitors. This study highlights the variability in the crystallization tendency of different compounds and provides insight into the mechanism of inhibition by polymeric additives. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:1981–1992, 2015